2010
DOI: 10.1105/tpc.110.075036
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis VASCULAR-RELATED NAC-DOMAIN6 Directly Regulates the Genes That Govern Programmed Cell Death and Secondary Wall Formation during Xylem Differentiation  

Abstract: Xylem consists of three types of cells: tracheary elements (TEs), parenchyma cells, and fiber cells. TE differentiation includes two essential processes, programmed cell death (PCD) and secondary cell wall formation. These two processes are tightly coupled. However, little is known about the molecular mechanisms underlying these processes. Here, we show that VASCULAR-RELATED NAC-DOMAIN6 (VND6), a master regulator of TEs, regulates some of the downstream genes involved in these processes in a coordinated manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
301
2
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(318 citation statements)
references
References 38 publications
9
301
2
6
Order By: Relevance
“…In Arabidopsis, MYB-type (MYB46, MYB58, and MYB63) and NAC-type (SND1, SND2, VND6, VND7, NST1, and NST2) transcription factors function as positive regulators of secondary cell wall synthesis. [18][19][20][21][22][23][24] Some rice NAC-type transcription factors have also been described to control secondary cell wall metabolism. 25 In rss3, several NAC genes that belong to the subfamily, in which Arabidopsis NST1 and SND2 are classified, were upregulated (Fig.…”
mentioning
confidence: 99%
“…In Arabidopsis, MYB-type (MYB46, MYB58, and MYB63) and NAC-type (SND1, SND2, VND6, VND7, NST1, and NST2) transcription factors function as positive regulators of secondary cell wall synthesis. [18][19][20][21][22][23][24] Some rice NAC-type transcription factors have also been described to control secondary cell wall metabolism. 25 In rss3, several NAC genes that belong to the subfamily, in which Arabidopsis NST1 and SND2 are classified, were upregulated (Fig.…”
mentioning
confidence: 99%
“…For example, in Arabidopsis, VASCULAR-RELATED NAC-DOMAIN6 (VND6) and VND7 regulate the development of metaxylem and protoxylem vessel elements, respectively (Kubo et al 2005;Yamaguchi et al 2008), while NAC SECONDARY WALL THICKENING PROMOTING FACTOR1 (NST1) and NST3 [also called SECONDARY WALL-ASSOCIATED NAC DOMAIN PROTEIN1 (SND1) or ARABIDOPSIS NAC DOMAIN CONTAINING PROTEIN012 (ANAC012)] redundantly act as master switches that turn on secondary wall formation in fibers (Mitsuda et al 2007;Zhong et al 2006). MYB46 and MYB83 are direct downstream transcription factors of VND6, VND7, NST1, and NST3/SND1/ANAC012 (McCarthy et al 2009;Ohashi-Ito et al 2010;Yamaguchi et al 2011). MYB46 and MYB83 can activate biosynthetic pathways for cellulose, xylan, and lignin, the three major secondary wall components (Ko et al 2009;McCarthy et al 2009;Nakano et al 2010;Zhong et al 2007).…”
mentioning
confidence: 99%
“…The functional suppression of VND6 and VND7 causes defects in the formation of vessel elements (Kubo et al 2005;Yamaguchi et al, 2008). Subsequently, Ohashi-Ito et al (2010) found that VND6 is a direct regulator of genes related to programmed cell death as well as to secondary wall formation. These results strongly suggest that VND6 and VND7 act as key regulators of xylem vessel differentiation.…”
Section: In Vitro Tracheary Element Systems In Herbaceous Angiospermsmentioning
confidence: 99%
“…Three common methods used to transform xylogenic lines are biolistic particle delivery (Ito and Fukuda 2002;Möller et al 2003;Wagner et al 2012), Agrobacterium tumefaciens-mediated transformation (Pyo et al 2007;Pesquet et al 2010;Ohashi-Ito et al 2010) and electroporation (Endo et al 2008).…”
Section: Tracheary Elements and Genetic Transformationmentioning
confidence: 99%